MINAT PENGGUNAAN SHOPEEPAYLATER PADA MAHASISWA AKUNTANSI DI JAKARTA SELATAN: ANTARA PENGETAHUAN AKUNTANSI SYARIAH DAN PERSEPSI RISIKO - Kartika Lisnawati; Husnul Khotimah (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2026)
Information technology advancements have impacted many facets of human existence, including the financial industry. The availability of digital payment services and online loans, which are becoming more and more common, particularly among the younger generation, is one of the new developments brought about by this growth. Shopee is one of the online platforms that has the most enthusiasts today, reaching 158 million visits per month. Shopee also provides payment methods that are easy to access such as the ShopeePayLater, ShopeePay, Cash On Delivery (COD) and Bank Transfer features. ShopeePayLater is one of the special features that is increasingly in demand by users. The purpose of this study is to determine how the influence of Islamic accounting knowledge and risk perceptions on interest in using ShopeePayLater on accounting students in South Jakarta. The method used in this research is quantitative by collecting data from 100 respondents through distributing questionnaires online on Google Form. Data testing in this study using SmartPLS 4.0 software. The results of this study are sharia accounting knowledge and risk perception have a positive and significant effect on interest in using ShopeePayLater.Keywords: Risk Perception; Sharia Accounting Knowledge; ShopeePayLater